2011
DOI: 10.1007/s11064-010-0388-8
|View full text |Cite
|
Sign up to set email alerts
|

The Activation of β2-Adrenergic Receptors in Naïve Rats Causes a Reduction of Blood Glutamate Levels: Relevance to Stress and Neuroprotection

Abstract: This study examines the effects of the activation of β1 and β2-adrenergic receptors on glutamate homeostasis in the blood of naïve rats. Forty five male Sprague-Dawley rats were randomly assigned into one of seven treatment groups that were treated with various β-adrenergic receptor agonist and antagonist drugs. Blood glutamate levels were determined at t = 0, 30, 60, 90, and 120 min. The activation of β1 and β2-adrenergic receptors via isoproterenol hydrochloride administration produced a marked sustained dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…Therefore, to reduce glutamate neurotoxicity, it was suggested that we regulate the levels of glutamate in the cerebrospinal fluid (CSF) and ECF by use of familiar mechanisms of glutamate transport from the brain to the blood. In our laboratory, we previously examined various mechanisms to lower glutamate levels including by activation of β 2 -adrenergic receptors and different kinds of hormones [21,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to reduce glutamate neurotoxicity, it was suggested that we regulate the levels of glutamate in the cerebrospinal fluid (CSF) and ECF by use of familiar mechanisms of glutamate transport from the brain to the blood. In our laboratory, we previously examined various mechanisms to lower glutamate levels including by activation of β 2 -adrenergic receptors and different kinds of hormones [21,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies done by our group and others have shown that pharmacologically reducing blood glutamate levels with glutamate scavengers (such as oxaloacetate and pyruvate) limit glutamate neurotoxicity and provide better neurologic outcomes after various brain insults, particularly traumatic brain injury [14,[19][20][21][44][45][46][47][48][49][50][51][52][53]. Unfortunately, although these treatments have been shown to be effective in animal models of stroke, traumatic brain injury, and subarachnoid hemorrhage, their use in humans is limited by Food and Drug administration restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…This is important for a number of reasons. One of them is the fact that serum glutamate is typically in the range 50–200 μm (Zlotnik et al 2011a, b, c) which is orders of magnitude higher than the concentrations that are toxic to neurons (Danbolt 2001). …”
Section: Glutamate Transporters At the Blood Brain Barriermentioning
confidence: 99%
“…This short-lived phenomenon may be related to activation of the sympathetic nervous system [27], possibly augmenting efflux of excess brain glutamate, contributing to the trend of spontaneous neurological improvement observed in all TBI groups 24 h post injury [16]. The significant increase of blood glutamate concentration at 60 min, ''overshooting'' baseline values, may reflect several processes, including overwhelming of the glutamate metabolism mechanisms and increased distribution from brain ECF and peripheral tissue into the blood [15,16,28].…”
Section: Discussionmentioning
confidence: 93%